Pengaruh Budaya Kerja dan Kompetensi Terhadap Kinerja Personel Bekangdam IV Hasanuddin - Haeruddin, Haeruddin; Ibrahim , Ibrahim; Horas, Erwin; Hamzah, Mukhtar (Al-Buhuts, 2023)
This study aims to analyze and understand the influence of work culture and competency on the performance of personnel in Bakangdam XIV Hasanuddin. The research approach employed is quantitative research. The population consists of 296 personnel from Bakangdam XIV Hasanuddin. Sample selection utilized the Slovin method with a sample size of 196 individuals. Data collection was carried out using a Likert scale ranging from 1 to 5. The questionnaire was distributed online through Google Forms. The analysis included tests for response characteristics, validity, reliability, and multiple linear regression. The research results reveal that work culture has a positive but nonsignificant effect on personnel performance, while competency has a positive and significant impact on personnel performance. Partial tests indicate that competency is the dominant variable, contributing to 90.5% of the influence on personnel performance. Simultaneously, both work culture and competency have a positive and significant combined effect of 58% on personnel performance, leaving the remaining 42% to other unexplored factors. Enhancing work culture and competency among personnel becomes crucial to elevate the performance of Bakangdam XIV Hasanuddin's personnel. The importance of these factors should be recognized, motivating all personnel to enhance their competency through continuous participation in training, upgrading, and higher education to ensure the continuous improvement of knowledge, skills, and positive attitudes.